2008
DOI: 10.1086/591976
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Significance of the Development and Anatomy of Flowers and Fruit of Quercus schottkyana (Subgenus Cyclobalanopsis: Fagaceae)

Abstract: The developmental process of flower and fruit production was studied for the first time in Quercus schottkyana (subgenus Cyclobalanopsis) and compared with other species of Quercus and related Fagaceae. Four main developmental periods were recognized, and standard embryological features such as basic type of anther wall formation, simultaneous cytokinesis of microspore mother cells, tetrahedrally arranged microspore tetrads, and two-to three-celled pollen grains. Polygonum type of embryo sac development, delay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Quercus. Subsequent work has shown that the position of aborted ovules in the mature seeds of Quercus is the result of different developmental processes and less stable than originally assumed (Borgardt and Pigg 1999;Borgardt and Nixon 2003;Deng et al 2008; Table 1).…”
Section: Change In Criteria For Classificationmentioning
confidence: 91%
“…Quercus. Subsequent work has shown that the position of aborted ovules in the mature seeds of Quercus is the result of different developmental processes and less stable than originally assumed (Borgardt and Pigg 1999;Borgardt and Nixon 2003;Deng et al 2008; Table 1).…”
Section: Change In Criteria For Classificationmentioning
confidence: 91%
“…Based on evidence from molecular phylogeny (Manos et al, 1999;Denk & Grimm, 2010), fossil records (Jones, 1986;Zhou, 1992) and morphological studies (Deng et al, 2008;Denk & Grimm, 2009), two subgenera of Quercus were identified. These studies suggested that subg.…”
Section: Species Distribution Datamentioning
confidence: 99%
“…Local weather influences pollination in some oaks through drought or temperature stress31 and also has a direct impact on the acorn crop size32. Pollination of Q. schottkyana generally occurs before mid-April33. After pollination, the warmer temperatures in May and June promote ovules and young fruit34.…”
Section: Discussionmentioning
confidence: 99%
“…Quercus schottkyana produces acorns annually and pollination occurs in the spring33. Acorns mature on the trees from late May to October and mature acorns fall to the ground between the end of August and mid-late November.…”
Section: Methodsmentioning
confidence: 99%